Online gaming with robots vs. computers as allies vs. opponents - Park, Eunil; Kim, Ki Joon; Sundar, S. Shyam; del Pobil, Angel P. (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
A 2 x 2 between-subjects experiment was conducted to examine the effects of the type of artificial agent (robot vs. computer) and the role of the agent (ally vs. enemy) on people's perceptions and evaluations of the agent when playing a video game. Participants perceived that playing the game with a robot was more enjoyable and easier than playing with a computer. Regardless of the agent type, participants reported that playing the game was more enjoyable when the agent played as an ally rather than as their opponent. Implications of notable findings are discussed.